A Feminist Liberation Framework for Responding to Intimate Partner Violence in Thailand. Issue 1 (3rd April 2021) - Chamsanit, Varaporn; Khuankaew, Ouyporn; Rungreangkulkij, Somporn; Norsworthy, Kathryn; M. Abrams, Elizabeth
Abstract: Using a feminist liberation framework, Thai mental health providers engaged in a structural and institutional analysis of intimate partner violence and developed a social justice based counseling approach based on their cultural contexts within Thailand. A Thai-centered power and control wheel was designed by project members for use in assessing and counseling survivors around the country. The coauthors, a Thai-U.S. team, describe the project methodology, which is informed by principles from liberation, post-colonial and decolonial frameworks, as well as transnational feminism, and is used in collaborating with participants to produce culture-centered knowledge and counseling approaches. Examples of how the Thai power and control is being utilized are provided.